EFFECT OF GUIDED EDUCATION ON PERCEPTION AND ATTITUDE OF CHILDBEARING WOMEN TOWARDS CAESAREAN SECTION IN NIGERIA - Mary Idowu Edward; Oluwaseun Segun Bolarinwa; Omowumi Suuru Ajibade; Temilola Mabel Aregbesola (OPI Napoli, 2023)
Background: Nigerian women are unwilling to have a Caesarean section because of the general belief that abdominal delivery is a reproductive failure on their part regardless of the feasibility of vaginal birth after Caesarean section and the decreasing mortality from Caesarean sections. Aim: The primary objective of this study was to investigate the existence of a significant relationship between pregnant women's knowledge and attitudes toward cesarean delivery before and after training. Materials and Methods: The study employed a pre/post-test study design, using questionnaires to obtain data from 152 childbearing women attending antenatal in Iloro Basic Health Centre, Akure, Ondo State. Descriptive statistics were used to summarize and present data. Associations between variables were tested using Spearman correlation at a p-value 0.05 level of significance. Results: The researcher found a significant relationship between the knowledge and attitude of pregnant women towards Caesarean section delivery before and after the training. The findings revealed an increase in the knowledge of mothers after the educational intervention, mothers would opt for a Caesarean section if it is necessary to protect them and the baby and they believe that it is a woman's right to choose a Caesarean section for herself. Significant relationship exists between knowledge and attitudes toward the Caesarean section. Conclusion: It was concluded that childbearing mothers still believe that vagina delivery is a natural delivery and there is joy attached to it, however, most women would still prefer vagina delivery to Caesarean section. The study recommends a need for awareness programs to enhance women's and the community positive perception towards the Caesarean section in Nigeria.